At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
[tex]\huge \fbox \pink {A}\huge \fbox \green {n}\huge \fbox \blue {s}\huge \fbox \red {w}\huge \fbox \purple {e}\huge \fbox \orange {r}[/tex]
[tex]x = 3[/tex]
[tex] {2x}^{3} + {x}^{2} - x \\ = 2(3) {}^{3} + (3) {}^{2} - 3 \\ = 2 \times {3}^{3} + {3}^{2} - 3 \\ = 2 \times 27 + 9 - 3 \\ = 54 + 9 - 3\\ = 63 - 3 \\ = 60 [/tex]
ʰᵒᵖᵉ ⁱᵗ ʰᵉˡᵖˢ
[tex] \huge\blue{ \mid{ \underline{ \overline{ \tt ꧁❣ ʀᴀɪɴʙᴏᴡˢᵃˡᵗ2²2² ࿐ }} \mid}}[/tex]
2x3 + x2 , x = 3
= 2*3*3 + 3*2
= 18 + 6
= 24
Hence 24 is the answer
= 2*3*3 + 3*2
= 18 + 6
= 24
Hence 24 is the answer
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.